Advanced multi-source converters for DC microgrids: integrating photovoltaic, wind, and hybrid storage systems - Neelagiri, Suganthi; Usha, Pasumarthi (Institute of Advanced Engineering and Science, 2025)
This paper presents a new configuration for integrating multi-source and hybrid energy storage (HES) systems tailored for a direct current (DC) microgrid. Unlike conventional multi-input converters, the proposed design features a hybrid energy storage system combining ultracapacitors and batteries. The proposed system is intended to effectively manage power variations from wind, photovoltaic (PV) sources, and abrupt load changes. The inclusion of ultracapacitors addresses high-frequency fluctuations, thereby extending battery life and reducing the overall size of the storage unit. The control framework is designed to maintain power balance within the system, ensuring that renewable energy sources operate at their maximum power points and that energy storage is efficiently charged and discharged based on power availability. The main advantages of this configuration include: i) a reduced number of switches, ii) built-in voltage boosting and regulation for the ultracapacitor, and power-sharing between the battery and ultracapacitor, and iii) a streamlined control system with fewer components. The paper details the investigation, modeling, and design of the planned system, supported by MATLAB simulation results.